A Framework for Researching Public Administration Decision Making Processes - Răzvan PETRUȘEL (Transylvanian Review of Administrative Sciences, 2013)
How decisions are made is a major concern for researchers and practitioners in public administration. So far, the approach to this problem was top-down. Researchers and practitioners were concerned with the legal framework, procedures and best practices of general applicability. Some of the issues tackled at the top level are: decisional transparency, citizens’ participation in public decisions, the legal procedures of public decision making etc. Research approaches rely on data gathered through surveys, questionnaires etc. Instead of using this general-to-particular approach, this paper argues that a bottom-up approach to researching public decision making processes is possible and valuable. Therefore, the main contribution of this paper is the introduction of a coherent framework, that enables research to be conducted based on automatic extraction of models from large numbers of individual cases of public decision making processes. Some of the research questions that could be answered by employing this framework are: ‘what was the actual decision process used for a particular decision?’, ‘is a particular decision process in line with the legal framework?’, ‘are two different decisions made based on the same process?’ etc. The framework that we introduce consists of a model that depicts the data-view of the decision making process and a methodology that enables such a model to be created from the data available in public municipalities. We also provide means to analyze the model in connection with case study data. The validation of the framework is done through a case study conducted at the level of Cluj-Napoca Municipality.